Fifty shades of ambivalence: South African student leaders’ belonging experiences as indigenous foreigners within higher education - Pule, Dr. Neo; Muleya, Mr. Vuyani; Flotman, Prof. Aden-Paul (Environment and Social Psychology, 2025)
The transformation of South African universities is complex because of the intersections of social, historical, political, cultural, and economic circumstances. Due to the transformation mandate, universities engage student leaders in co-governance to facilitate collaborative efforts toward establishing a sense of belonging for student leaders. However, the complexity of the environment and the transformation task create discrepancies that affect student leaders’ sense of belonging. Therefore, this article explores South African student leaders’ sense of belonging in the university, using socioanalysis. We gathered verbal and visual data through social dream drawing with student leaders to present an account of their conscious and unconscious lived experiences of belonging. We used thematic analysis to organize the identified themes and sub-themes and interpreted them using a socio-analytic understanding. The findings suggest that student leaders experience belonging paradoxically as “indigenous foreigners” in higher education, but also ambivalently, hence the reference to Fifty shades of ambivalence in the title. They perceive membership dynamics in various ways: as fluid belonging, with strings attached, as complicated bonding, and as the paradoxical dance between dominance and submission, as well as connecting to shades of legacies and patrimony. We argue that learning about student leaders’ sense of belonging through social dream drawing enhances their leadership agency and facilitates a co-productive, collaborative, and active participation strategy. This process strengthens co-governance practices on multi-relational levels and multiple domains of belonging. Thus, dynamically understanding student leaders’ sense of belonging produces positive outcomes for academic structures and integration processes through innovative student engagement.